Growth of Indigofera zolingeriana with differences in source of cuttings and planting media - Merani, Jeki Romelus; Rumetor, Sientje D.; Sawen, Diana (Fakultas Peternakan Universitas Papua, 2024)
This study investigates the effect of different cutting types and planting media on the growth of Indigofera zollingeriana, a valuable forage crop. The research used a factorial randomized block design (2 x 2) with 40 experimental units. The treatments included two cutting sources—stem cuttings (A1) and shoot cuttings (A2)—and two planting media—natural soil (B1) and natural soil supplemented with liquid organic fertilizer from rabbit urine (B2). Growth parameters such as the number of leaves, plant height, and stem diameter were measured. The results indicate that cutting type significantly affects leaf production, with shoot cuttings (A2) producing a higher number of leaves than stem cuttings (A1) (P<0.05). However, the planting media and its interaction with the cutting type had no significant impact on plant height and stem diameter (P>0.05). These findings suggest that using shoot cuttings could enhance the propagation and growth of Indigofera zollingeriana for sustainable forage production. Further studies are recommended to explore the long-term effects of organic fertilizer on biomass yield.